PENGARUH WUJUD NYATA DAN DAYA TANGGAP PADA BAGIAN HUMAS KABUPATEN WONOGIRI TERHADAP KEPUASAN MASYARAKAT - Mulyanto, Yuni Indarti & (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2012)
ABSTRACT This study aims to determine the correlation between Tangibles, Responsiveness and Organizational Culture to the Community Satisfaction and determine the correlation between Tangibles and Responsiveness to the Cultural Organization in Public Relations’ Services to the Society of Wonogiri. The samples are 150 respondents, comprising employees in the SKPD, BUMN/ BUMD and organizations in Wonogiri. The data derived from the primary data trough endorsement of questionnaires to respondents. And the secondary data through literature study. Data analysis was performed through analysis of research instruments including the test of validity by using the product moment method; the test reliability using Cronbach's Alpha and technical analysis using path analysis. Total value of R2 is 86,3% meaning satisfaction portrays the Tangibles, Responsiveness and Cultural Organization as an intervening variable for the remaining 86,3%. The results tangible variable indirectly affects to satisfaction score of 0,485. Meanwhile, responsiveness variable directly affects to satisfaction score of 0,698. Keywords: tangibles, responsiveness, public satisfaction